Synchronization of Synthetic Insecticides with Aggregation Pheromone Against Rhynchophorus ferrugenius (Oliver).: Compatibility of Ferrolure+ with Insecticides (Biological Sciences - PJSIR, 2024)
Aggregation pheromone (ferrolure+) has the potential for successful detection, monitoring and management of Red palm weevil (RPW), Rhynchophorus ferrugenius. Therefore, studies were undertaken to evaluate the effectiveness of aggregation pheromone (ferrolure+) along with synthetic insecticides i.e., Karate 0.25 EC (Lambda-cyhlothrin), Coragen 20SC (Chlorantranliprole), Curacron 50 EC (profenophos), Steward 150EC (indoxacarb) and Talstar 10EC (bifenthrin) for the management of RPW. Control treatments with and without ferrolure+ were also maintained. Four traps per acre were applied in each study arranged in a randomized complete block design. Weekly observations were taken till the effectiveness of ferrolure+. Results confirmed that addition of synthetic insecticides showed a negative impact on the mean capture of RPW except for indoxacarb (7.59±0.89 weevils per trap) that attract significantly same but comparatively less RPW attracted towards only ferrolure+ pheromone traps (8.74±0.96 weevils per trap). Overall RPW captured in remaining treatments i.e., chlorantranliprole, lambda-cyhlothrin, profenophos and bifenthrin were 4.56+0.65 weevils per trap; (5.22+0.69) weevils per trap; 5.63+0.71 weevils per trap and 5.48+0.89 weevils per trap, respectively. A gradual rise was recorded in mean capture of RPW in all treatments till week five after installation and then declined rapidly upto week eight. More than double number of females were captured in traps with maximum male to female ratio (1:2.26) captured in lambda-cyhlothrin treatment. Therefore, it is suggested that ferrolure+ traps should be included in the integrated management programs of RPW and indoxacarb pesticide, if required, may be added in trap to get maximum killing of weevils, particularly females that will also help reduce future population growth.